Nutritional Bioactive Compounds and Health Benefits of Fresh and Processed Cucumber (Cucumis Sativus L.) - Uthpala, T. G. G; Marapana, R. A. U. J; Lakmini, K. P. C; Wettimuny, D. C. (Journal of Biotechnology, 2020)
Gherkin (Cucumis sativus L.) generally known as commercial cucumber, is native to the region of Asia, and is now widely cultivated in many other parts of the world to be sold fresh and for pickle production. Cucumber is a rich source of valuable nutrients and bio active compounds and is used not only as food but also in therapeutic medicine and cosmetology. Cucumber is considered as a vegetable crop and is rich in polyphenolics and cucurbitacins, that are known to possess multiple biological activities such as antioxidant, anti-carcinogenic, anti-hyaluronidase, anti-elastase, antiinflammatory, anti-hyperglycemic, diuretic, amylolytic, antimicrobial, and analgesic effects. Fruits that are preserved by dipping in a solution of salt or vinegar that undergo a fermentation process are known as pickles. Since, pickling of gherkins enhances the flavor, texture, and nutritional aspects, it is also very popular for its nutritive and health-promoting potential; especially against diabetes complications and cardiovascular disorders due to the presence of monounsaturated fats and other valuable minor components such as phenolics etc. The variety, geographic location of production, harvest time, and the processing techniques practiced are some of the factors shown to influence the composition of cucumber. This review focuses comprehensively on the nutrients and high-value bio active compound profile as well as medicinal and functional aspects of fresh and processed cucumber. Multiple benefits associated with the phytochemical and nutritional composition of this food commodity are also discussed in the following sections.
Keywords: Cucumber; Gherkin; Cucurbitacins; Phytochemicals; Antioxidants; Health benefits.